2022
DOI: 10.3897/subtbiol.42.78037
|View full text |Cite
|
Sign up to set email alerts
|

Transitional and small aquatic cave habitats diversification based on protist assemblages in the Veternica cave (Medvednica Mt., Croatia)

Abstract: Protists in caves are scarcely researched. Most cave studies address the diversity of protists, but very little is known about their habitats and spatio-temporal dynamics. The aim of this study was to investigate the diversity and abundance of protists in the Veternica cave in the Medvednica mountain in Croatia on hygropetric and sinter and clay pools during six months. During this study, 47 protists taxa were distinguished belonging to the groups of heterotrophic flagellates, ciliates, heliozoans, stramenopil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is likely that the high phosphate concentration at Krka spring originated from groundwater and promoted algal and microbial growth supporting colonial, bacterivorous, filter-feeding ciliates. Baković et al [77] already found that karst underground habitats of Croatia and Bosnia and Herzegovina are a hotspot of protist biodiversity; therefore, it is likely that the influx of groundwater served as a mechanism of ciliate colonization at Krka spring. Interestingly, Kulaš et al [78] recorded diatom species (Aulacoseira granulata (Ehrenberg) Simonsen and Navicula cryptotenella Lange-Bertalot) at Krka spring that tolerate higher phosphate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the high phosphate concentration at Krka spring originated from groundwater and promoted algal and microbial growth supporting colonial, bacterivorous, filter-feeding ciliates. Baković et al [77] already found that karst underground habitats of Croatia and Bosnia and Herzegovina are a hotspot of protist biodiversity; therefore, it is likely that the influx of groundwater served as a mechanism of ciliate colonization at Krka spring. Interestingly, Kulaš et al [78] recorded diatom species (Aulacoseira granulata (Ehrenberg) Simonsen and Navicula cryptotenella Lange-Bertalot) at Krka spring that tolerate higher phosphate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been some reports on the protist diversity from Mexican caves located in the states of San Luis Potosí (Cueva de Los Riscos cave) and Guerrero cave (Osorio-Tafall 1943;Hoffmann et al 1986;Sigala-Regalado et al 2011), from Slovenian karst caves (Walochnik and Mulec 2009), and from caves in North America (Holsinger 1966;Barr 1968;Hill et al 1986;Small et al 1986). More recently, Baković et al (2022) investigated the protists of three habitats within the Veternica Cave (Croatia) and reported 47 protist taxa, including 16 ciliates. Regarding Italian caves, Guidolin (1999, 2003) recorded over 100 ciliates from karst caves in Northeast Italy, most of which were new to the Italian checklist (http://www.faunaitalia.it/checklist/).…”
Section: Ciliate Community Structure: Species Richness Taxonomic and ...mentioning
confidence: 99%
“…Groundwater is a highly diverse ecosystem, hosting over 7000 known animal species currently extinct on the surface (mostly arthropods 12 ) and 2–6 × 10 26 cells of microorganisms (prokaryotes 13 ; fungi and a viral repository 14 ), compressed into just ~ 19% of the world’s area 15 . Groundwater-adapted biodiversity is mainly composed of short-range species with restricted distributions [e.g.…”
Section: Introductionmentioning
confidence: 99%